ANALYSIS OF USING CHEMICAL LABORATORY IN SMA STATE EAST KALIMANTAN - Muh. Amir M (PROSIDING SEMINAR KIMIA, 2015)
The aims of this research is to described the use of instructional media and chemical laboratory chemistry on high school students in East Kalimantan. The method that used in this researchis a qualitative approach because it used the data source directly as a scientific background. The subject of this study are; 1) the principal, 2) vice curriculum 3) teachers 4) students, who knowed and can be trusted to be the source of the data and determine the depth of the problems study. The source of the data is the Education Unit Level High School in East Kalimantan. The resulted of laboratory research to the design aspects related with layout, number and arrangement of space inside the laboratory has good criteria with the percentage is 74.39%. Administrative aspects indicated have obstacles in that and this is in accordance to the results of interviews and direct observation, with percentage is 66.30%. Lab administration has good enough criteria differently with other aspects that reached a percentage is over 70%. Practical aspects of the management in the provision relatedis how the course of events before and after the practicum takes place based on the supporting data reached a percentage is 79.94%. From this percentage showed that practicum implementation has been very ready. Completed aspects of tools and materials, which reached up to 90% with very good prepared of criteria, it is in accordance with the observational data that showed the tool and the material in the chemical laboratory has been standardized school laboraotrium. Thus, the implementation of the learning process average teacher in every teaching chemistry using the media as a supported of teaching and learning so that students are very enthusiastic, especially increasing the activity and motivation during the lesson.